Alcohol detection using Arduino with motor locking - Fahteem Hamamy; Ahmad Adib Danial (Journal of Engineering Technology, 2022)
The identification of alcohol with the locking mechanism of the engine decreases the spike of road accidents caused by drivers’ extreme alcohol intake. The device controls alcohol in the driver’s exhaled breath to activate the engine locking system. Alcohol sensor Arduino Mega microcontroller, DC motor, is used for system creation. The car engine is switched off, and the emergency siren is blown as soon as alcohol is detected, minimizing the likelihood of any potential mishaps. The prototype is also useful for preventing a catastrophic driver-induced crash. Previously, there was no technology to lock the vehicle engine after the alcohol was detected. Driver alcohol consumption too much, which was the main cause of the accident. It was the same manual checks after a particular distance on streets or freeways, but they will never be enough to halt the malfunctions. Driving any vehicle in a developing country like Malaysia takes great dedication, rapid thought, and drivers’ judgment talents to help stop traffic accidents. Getting drunk alcohol beyond a certain quantity distorts a driver’s standard brain function and mentality, which often leads to accidents that impact not only the driver but also his fellow passengers and people nearby. In turn, the family members may also suffer from fatal trauma. The proposed device would measure the many conditions that can cause an alarm to signify the driver’s drunk or sober state when fitted on a steering wheel within the car. For the recommendation to improve the project in the future, particularly in preventing system cheats and device damage. Concerning anti-cheating, one common approach to cheating the device is to request another person to take a clean sample of a breath when starting the car. The recommended advancement and generations to work to mitigate this problem involve a face lock application for security to ensure that the car is the authorized driver taking the check procedure.